Psychological symptoms and their correlates in pneumoconiosis patients: a bilingual scoping review - Wang, Xi-Ping; Li, Runxuan; Tam, Kim-Pong (Frontiers in Public Health, 2025)
PurposePneumoconiosis remains a global occupational and public health problem. This scoping review is aimed to identify the psychological symptoms and their correlates among pneumoconiosis patients.MethodsWe conducted a bilingual scoping review following the PRISMA-ScR guidelines. Studies published between 2000 and 2025 were identified through searches of English-language (PubMed, Web of Science, Scopus, ScienceDirect) and Chinese-language (CNKI, CBM, Wanfang, VIP) databases, using English and Chinese descriptors related to pneumoconiosis and psychological symptoms. The search was conducted from June 28 to July 5, 2025. Peer-reviewed empirical studies that reported quantitative psychological outcomes among patients diagnosed with pneumoconiosis were included.ResultsA total of 55 studies were included in this review: 11 in English and 44 in Chinese. Considerable variability in reported prevalence was observed, primarily driven by differences in the instruments used and the cutoff criteria. For depression, with different diagnostic tools and criteria, Chinese studies reported prevalence ranging from 16.3% to 87.22%, and English studies reported prevalence ranging from 75.2% to 86.1%. For anxiety, again with varying assessment tools and criteria, Chinese studies reported rates from 9.5% to 61.97%, and English studies reported rates from 75% to 99.1%. Some studies also reported somatisation, obsessive-compulsive symptoms, and sleep disturbances. Key correlates associated with these symptoms included biological, social, and psychological factors.ConclusionThis review synthesises evidence on the high prevalence of psychological symptoms among pneumoconiosis patients across diverse regions, which are associated with multifaceted factors. The scarcity of intervention studies, combined with methodological heterogeneity in existing research, underscores the urgent need for standardized assessment tools and the development of context-sensitive, biopsychosocial care models for this population.